Assessment of anthropogenic-causing-agents act on waterbirds-diversity in the vicinity of Tarbela Dam, Indus River, Pakistan - Rahman,Q. (2024)
Abstract Birds are among the best bio-indicators, which can guide us to recognize some of the main conservation concerns in ecosystems. Anthropogenic impacts such as deforestation, habitat degradation, modification of landscapes, and decreased quality of habitats are major threats to bird diversity. The present study was designed to detect anthropogenic causative agents that act on waterbird diversity in Tarbella Dam, Indus River, Pakistan. Waterbird censuses were carried out from March 2019 to February 2020 in multiple areas around the dam. A total of 2990 waterbirds representing 63 species were recorded. We detected the highest waterbird richness and diversity at Pehure whereas the highest density was recorded at Kabbal. Human activity impacts seemed to be the main factor determining the waterbird communities as waterbirds were negatively correlated with the greatest anthropogenic impacts. Waterbirds seem to respond rapidly to human disturbance.